Comparative transcriptomics characterized the distinct biosynthetic abilities of terpenoid and paeoniflorin biosynthesis in herbaceous peony strains - Lu,Baowei; An,Fengxia; Cao,Liangjing; Gao,Qian; Wang,Xuan; Yang,Yongjian; Liu,Pengming; Yang,Baoliang; Chen,Tong; Li,Xin-Chang; Chen,Qinghua; Liu,Jun (PeerJ, 2020)
The herbaceous peony (Paeonia lactiflora Pall.) is a perennial flowering plant of the Paeoniaceae species that is widely cultivated for medical and ornamental uses. The monoterpene glucoside paeoniflorin and its derivatives are the active compounds of the P. lactiflora roots. However, the gene regulation pathways associated with monoterpene and paeoniflorin biosynthesis in P. lactiflora are still unclear. Here, we selected three genotypes of P. lactiflora with distinct morphologic features and chemical compositions that were a result of long-term reproductive isolation. We performed an RNA-sequencing experiment to profile the transcriptome changes of the shoots and roots. Using de novo assembly analysis, we identified 36,264 unigenes, including 521 genes responsible for encoding transcription factors. We also identified 28,925 unigenes that were differentially expressed in different organs and/or genotypes. Pathway enrichment analysis showed that the P. lactiflora unigenes were significantly overrepresented in several secondary metabolite biosynthesis pathways. We identified and profiled 33 genes responsible for encoding the enzymescontrolling the major catalytic reactions in the terpenoid backbone and in monoterpenoid biosynthesis. Our study identified the candidate genes in the terpenoid biosynthesis pathways, providing useful information for metabolic engineering of P. lactiflora intended for pharmaceutical uses and facilitating the development of strategies to improve marker-assist P. lactiflora in the future.
Keywords: RNA-seq; Terpenoid biosynthesis; Monoterpene; Paeoniflorin; Paeonia lactiflora Pall